PRESCRIPTION PATTERN OF ANTIBIOTICS AND THEIR APPROPRIATENESS IN PATIENTS WITH CHRONIC KIDNEY DISEASE-AN OBSERVATIONAL STUDY IN A TERTIARY CARE TEACHING HOSPITAL IN SOUTH INDIA - CHALIVENDRA, PALLAVI; K., UMAMAHESWARA RAO; SUCHARITHA, J; CHANDRA, VURIMI BHOPAL; NELAVALA, ANJANI DEVI (International Journal of Current Pharmaceutical Research, 2023)
Objective: The primary objective of the study was to assess the prescribing pattern of antimicrobial agents in patients with chronic kidney disease. The secondary objectives of this study are to assess antibiotic appropriateness and dose optimization in patients with chronic kidney disease in relation to their comorbidities. Methods: A retrospective study was conducted, and medical records of all patients with CKD who were admitted in the nephrology department of Sri Venkateswara Institute of Medical Sciences, Tirupati, during Jan 2018-Dec 2018 were reviewed for antibiotic prescriptions. A total of 200 medical records were selected and assessed for antimicrobial prescriptions. A p-value <0.05 was considered significant throughout the statistical analysis. Results: Analysis showed that overall 163 drugs were prescribed to CKD patients, of which nearly 96 (58.9%) required dosage adjustment. Of those 163 drugs, the majority N= 25 (26%), were unadjusted, and the remaining N = 71 (74%) were properly adjusted. The length of hospitalization of CKD patients was below 7 was 13.5%, above 7 was 86.5%. Mean and SD was 10.27±7.18 d, (Range: 1–35 d). The Chi-square analysis confirmed that out of the seven studied variables, two i.e. Length of stay days; p<0.001. Conclusion: It is concluded that the occurrence of medication dosing errors was moderate in hospitalized chronic kidney disease patients in our study. Nearly 20% of patients who had prolonged stays were prescribed antibiotics for a prolonged period. The predictors of medication dosing errors in CKD patients were the severe-to-end stages of chronic kidney disease, the number of prescribed antibiotics, and the length of hospitalization.